Molecular-driven treatment for biliary tract cancer: the promising turning point. Issue 11 (2nd November 2021) - Persano, Mara; Puzzoni, Marco; Ziranu, Pina; Pusceddu, Valeria; Lai, Eleonora; Pretta, Andrea; Donisi, Clelia; Pinna, Giovanna; Spanu, Dario; Cimbro, Erika; Parrino, Alissa; Liscia, Nicole; et al.
ABSTRACT: Introduction: In the past, targeted therapies have not shown positive results as they have been used without adequate molecular selection of patients with biliary tract cancer (BTC). This has led to an expansion of research on characteristics and molecular selection to identify new effective strategies in this setting. Improved knowledge of the molecular biology of these neoplasms has highlighted their extraordinary heterogeneity and has made it possible to identify targetable gene alterations, including fibroblast growth factor receptor (FGFR) 2 gene fusions, and isocitrate dehydrogenase (IDH) mutations. The FDA recently approved ivosidenib and pemigatinib for the treatment of BTCs. Areas covered: We review data in the literature regarding targeted therapies for the treatment of BTCs, as well as on the prospects deriving from the extraordinary molecular heterogeneity of these neoplasms. Expert opinion: At present, it is essential to evaluate the expression of the genetic alterations expressed by these neoplasms to offer patients an increasingly personalized therapeutic approach. Studies are needed to better define the limits and potentials of targeted therapies and their role in the therapeutic algorithm to improve the poor prognosis of these patients.